Validación de genotipos de frijol negro en la zona central del estado de Veracruz, México. - Ugalde-Acosta, Francisco Javier; López Salinas, Ernesto; Tosquy-Valle, Oscar Hugo (Agronomía Mesoamericana, 2005)
Validation of genotypes of black bean in the central area of the state of Veracruz, Mexico. The aims of this work was to validate bean growers’ fields. During 1998 to 2001 residual moisture growing cycles, nine validation plots were established. The bean genotypes utilized were: the lines II-307 and DOR-500 and the varieties Negro Huasteco 81, Negro Cotaxtla 91, Negro INIFAP and Jamapa, which is traditionally sown by beans growers. All the materials were handled with the agronomical recommendations of INIFAP for that bean growing area. Each plot had an area of 3000 m2. Individual analyses of variance by locality were performed. The yields obtained for each genotype (500m2) in one evaluation cycle were considered as replications. Combined analyses using the Marginal Return Rate were also performed. The results indicated that the yields of the varieties and improved lines were 100% higher than the yield of the traditional variety. The economic analysis showed that the highest economic profit was obtained when varieties Negro INIFAP and Negro Cotaxtla 91 were sown, being their profits higher than $3000/ha and having a profit/cost relationship of 1.52 and 1.51, respectively.